Cross‐national comparison of factors related to stressors, burnout and turnover among nurses in developed and developing countries - Takashi Ohue; Supaporn Aryamuang; Laura Bourdeanu; Jean N. Church; Hamidah Hassan; Jaruwan Kownaklai; Arlene Pericak; Amorn Suwannimitr (Wiley, 2021)
Abstract Aim To examine factors of a hypothetical model related to stressors, burnout and turnover in nurses from developed and developing countries-Canada, Japan, the United States, Malaysia and Thailand. Design A cross‐sectional questionnaire‐based study. Methods Conducted between April 2016 and October 2017, the Maslach Burnout Inventory, Intention to Leave Scale, and Nursing Stress Scale collected data from acute care hospital nurses in Canada (n = 309), Japan (n = 319), Malaysia (n = 242), Thailand (n = 211) and the United States (n = 194). Results Compared to other countries, burnout "exhaustion" was the highest in Japan and "cynicism" and intention to leave the job were the highest in Malaysia. Thailand had lower burnouts and turnover than other countries and higher professional efficacy than Japan and Malaysia. In all countries, reducing stressors is important for reducing burnout and intention to leave jobs, especially as they relate to "lack of support."